Identification of Vegetable Food Consumed by Tobelo People in Lina Ino Village, Tobelo Tengah Sub-District - Patty, Zeth; Kastanja, Ariance Yeane; Paulus, Fredi Jakson (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This research was carried out for 3 months in Lina Ino Village with the aim of identifying types of vegetable foods which include sources of carbohydrates, proteins and vitamins consumed by the people of Lina Ino Village, Central Tobelo. The location of the study was determined deliberately, with a sample of 85 respondents from 591 households. Data was collected through an interview method using a list of questions, which included types of vegetable food sources of carbohydrates, proteins and vitamins, sources of food ingredients and processing methods. The results showed that the people of Lina Ino Village consumed 5 types of carbohydrates, 3 types of legumes sources of protein. 9 types of vegetables consumed as a source of vitamins and minerals, consisting of 3 leaf vegetables, 2 types of fruit vegetables, 1 type of legume vegetables and 2 types of vegetables consumed leaves and fruits, and 4 types of fruit. Some food sources are obtained by buying from retailers while others are grown in community gardens. Food processing carried out is generally divided into 3, namely, boiled, fried, and cooked in coconut milk.